2022
DOI: 10.1055/s-0042-1749649
|View full text |Cite
|
Sign up to set email alerts
|

Preanesthetic Evaluation and Preparation for Neurosurgical Procedures: An Indian Perspective

Abstract: Background A questionnaire-based survey was conducted to determine the preanesthetic evaluation (PAE) practices among the members of the Indian Society of Neuroanesthesiology and Critical Care (ISNACC). The survey aimed to assess the current clinical practice of PAE and optimization of neurosurgical patients in India. Methods An online questionnaire was designed by the working group of ISNACC and circulated among its active members. Response to individual questions was considered significant if 50% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…4 Terdapat berbagai macam tumor otak yang biasanya ada bersamaan dengan aneurisma serebri, mulai dari meningioma, adenoma pituitari, glioma, lipoma, dan tumor metastasis. 5 Rencana anestesi pada kondisi 2 patologi otak ini membutuhkan pemahaman terkait penyakit neurovaskular dan prosedur pembedahan terkait. Kondisi pembuluh darah pasca kliping harus tetap diwaspadai, karena rentang keamanan yang cukup sempit antara tekanan darah yang tinggi yang dapat menyebabkan pecah pembuluh darah serta rendahnya tekanan darah yang dapat menyebabkan iskemia otak.…”
Section: Pendahuluanunclassified
“…4 Terdapat berbagai macam tumor otak yang biasanya ada bersamaan dengan aneurisma serebri, mulai dari meningioma, adenoma pituitari, glioma, lipoma, dan tumor metastasis. 5 Rencana anestesi pada kondisi 2 patologi otak ini membutuhkan pemahaman terkait penyakit neurovaskular dan prosedur pembedahan terkait. Kondisi pembuluh darah pasca kliping harus tetap diwaspadai, karena rentang keamanan yang cukup sempit antara tekanan darah yang tinggi yang dapat menyebabkan pecah pembuluh darah serta rendahnya tekanan darah yang dapat menyebabkan iskemia otak.…”
Section: Pendahuluanunclassified
“…The information collected is published in the current issue of Journal of Neuroanesthesiology and Critical Care (JNACC). 1 In neurosurgical literature, several studies reported many preoperative predictive factors that influence the outcome of the patients. These factors have to be given due importance in the preoperative assessment of a neurosurgical patient.…”
mentioning
confidence: 99%